Death, After-Life and Rebirth: Cultural Transfusion of Ideas - Petkova, Diana (Funes. Journal of narratives and social sciences, 2018)
On the basis of a cross-cultural comparative analysis this paper studies the ideas of death and rebirth in two cultures – India and Bulgaria. The results of the empirical research show that there is a significant shift in the perception of religion in the two countries. In Hinduism the phenomenon of death is tightly intertwined with the concepts of karma and reincarnation. Although it has been an ancient tradition in India there are many people nowadays who do not share the belief in reincarnation. While in Bulgaria, where the Christian church has officially denied the existence of rebirth, this concept is not so unusual. Thus, in postmodernity there is a process of cultural transfusion of ideas, in which new beliefs are incorporated into old traditional systems. In this way, the old systems of thought are rejuvenated, so that individuals gain sense, meaning and purpose in their lives. The paper also investigates the interrelation between the concepts of fate/karma, on the one hand, and death, on the other. In outlining the postmodern thinking, the paper also introduces the concept of “cultural transfusion”, designating with this term the incorporation of new ideas into old belief systems without the latter to undergo significant or major transformations.